(untitled) (Collection of scientific works «Scientific Problems of Architecture and Urban Planning» | ODABA, 2026)
The paper examines the problem of misalignment between design and cost documentation as one of the key causes of cost overruns, schedule deviations, and reduced transparency in construction project management. It is shown that conventional estimating approaches based on manual or semi automated quantity take off from drawings generate cost documentation as an autonomous information product weakly connected to design data, which leads to repeated recalculations of quantities and costs and to the accumulation of errors when design changes occur. A BIM oriented approach using 5D BIM is substantiated, within which geometric, quantitative, and cost parameters are integrated into a single information model and maintained as controlled versioned data. The role of Quantity Take Off and Bill of Quantities processes is clarified, where QTO provides continuous extraction of quantitative indicators directly from model element parameters, while BOQ forms a structured document for cost calculations and contractual interaction. It is demonstrated that the information model as a single reliable source of data enables scenario based estimating, early comparison of alternative technical solutions, and prompt assessment of the cost impact of design changes. The prerequisites for effective implementation of 5D BIM in national practice are identified, including standardization of information requirements, classification systems, and change management in accordance with ISO 19650 principles. The obtained findings may be applied in practice through the use of artificial intelligence tools within BIM oriented cost management systems.